Multidisciplinary Approach In Advanced Perivascular Epithelioid Cell Tumour (PEComa): A Case Report - Panebianco, Martina; Ierinò, Debora; Milano, Annalisa; D’Antonio, Chiara; Aschelter, Anna Maria; Marchetti, Paolo (Archives of Clinical and Medical Case Reports, 2021)
Background: Perivascular epithelioid cell tumours (PEComas) are mesenchymal neoplasms with variable biological behaviour, ranging from benign to extremely aggressive diseases able to metastasize. No prospective studies are available to define a validate approach to this type of tumours. Case presentation: We present a case report of a 53-year-old woman affected by advanced retroperitoneal PEComa who developed an abdominal disease progression after 40 months of therapy with mTOR inhibitor. The patient underwent cyto-reductive surgery followed by radiotherapy on the residual disease and started chemotherapy with olaratumab plus doxorubicin for seven cycles achieving a partial response so she continued monotherapy with olaratumab for one year with stable disease to quarterly CT evaluation. On September 2019 treatment was definitely interrupted because of marketing authorisation of olaratumab was revoked due to insufficient proof of its medical advantage in phase III trial ANNOUNCE. Currently the patient is still in follow up after 18 months from the interruption of therapy, without a disease progression. Discussion and Conclusion: In our PEComa clinical case, we highlight how a multidisciplinary approach can lead to disease control and a long clinical benefit.